El filológo Pedro Urbano González de la Calle (1879-1966). Una aproximación a su vida y obra - Protomártir Vaquero, Santos M. (El Colegio de México, 2017)
Reception: July 6, 2016Accepted: April 25, 2017This paper traces the career of the Spanish philologist Pedro Urbano González de la Calle (1879-1966), from his early years as professor of Latin Philology at the University of Salamanca and the Central University of Madrid through to his later experience as an exile living in Colombia and Mexico. Importance is placed on his early work on Francisco Sánchez de las Brozas “El Brocense” and other Spanish Renaissance humanists, as well as on his subsequent research relating to the work of the Colombian linguist Rufino J. Cuervo. The paper closes with a list of his principal publications.